Macrophage Heterogeneity in Kidney Injury and Fibrosis - Wen, Yi; Yan, Hong-Ru; Wang, Bin; Liu, Bi-Cheng (Frontiers in Immunology, 2021)
Kidney macrophages are central in kidney disease pathogenesis and have therapeutic potential in preventing tissue injury and fibrosis. Recent studies highlighted that kidney macrophages are notably heterogeneous immune cells that fulfill opposing functions such as clearing deposited pathogens, maintaining immune tolerance, initiating and regulating inflammatory responses, promoting kidney fibrosis, and degrading the extracellular matrix. Macrophage origins can partially explain macrophage heterogeneity in the kidneys. Circulating Ly6C+ monocytes are recruited to inflammatory sites by chemokines, while self-renewed kidney resident macrophages contribute to kidney repair and fibrosis. The proliferation of resident macrophages or infiltrating monocytes provides an alternative explanation of macrophage accumulation after kidney injury. In addition, dynamic Ly6C expression on infiltrating monocytes accompanies functional changes in handling kidney inflammation and fibrosis. Mechanisms underlying kidney macrophage heterogeneity, either by recruiting monocyte subpopulations, regulating macrophage polarization, or impacting distinctive macrophage functions, may help develop macrophage-targeted therapies for kidney diseases.